LOSING SMALL WARS : BRITISH MILITARY FAILURE IN IRAQ AND AFGHANISTAN - Ledwidge, Frank (Yale University Press, 2011)
Partly on the strength of their apparent success in insurgencies such as Malaya and Northern Ireland, the British armed forces have long been perceived as world class, if not world-beating. However, their recent performance in Iraq and Afghanistan is widely seen as - at best - disappointing; under British control, Basra degenerated into a lawless city riven with internecine violence, while tactical mistakes and strategic incompetence in Helmand province resulted in heavy civilian and military casualties and a climate of violence and insecurity. In both cases the British were eventually and humiliatingly bailed out by the US army. In this thoughtful and compellingly readable book, Frank Ledwidge examines the British involvement in Iraq and Afghanistan, asking how and why it went so wrong. With the aid of copious research, interviews with senior officers and his own personal experiences, he looks in detail at the failures of strategic thinking and culture that led to defeat in Britain's latest 'small wars'. This is an eye-opening analysis of the causes of military failure, and its enormous costs.